(untitled) (Boston, 2006)
James West Davidson received his B.A. from Haverford College and his Ph.D. from Yale University. A historian who has pursued a full-time writing career, he is the author of numerous books, among them After the Fact: The Art of Historical Detection (with Mark H. Lytle), The Logic of Millennial Thought: Eighteenth Century New England, and Great Heart: The History of a Labrador Adventure (with John Rugge). He is co-editor with Michael Stiff of the Oxford New Narratives in American History, in which his most recent book appears: 'They Say': Ida B. Wells and the Reconstruction of Race
Keywords: United States,Hoa Kỳ; History,Lịch sử